Apakah Karyawan Berubah pada Saat Perubahan Organisasi? Peran Moderasi Working Condition Pada Pengaruh Kepemimpinan Transformasional Terhadap Sisnisme Pada Perubahan Organisasi - Zainur Rahman (Jurnal Perilaku dan Strategi Bisnis, 2022)
The aims of this study to analyze the effect of transformational leadership toward cynicism about organizational change. This article also used working condition as moderating variable to test the transformational leadership and cynicism about organizational change linkage. This study uses a quantitative approach by using surveys to collect the data. The sampling technique used purposive sampling and the creteria of this respondent were the employee who working in the organization for organizational changing process. The total of a sample size were 141 respondents in the service sector. This study proved that transformational leadership has a negative effect on cynicism about organizational change. Working condition moderate the effect of transformational leadership toward cynicism about organizational change. Transformational leadership was characterized by the ability of leader to stimulate and motivate their follower to face the changing process in positive view. Beside, the leaders has the ability to share the vision and the goal of organization clearly to their follower. The effect of transformational leadership was stronger by the working condition as moderating variable.